2021
DOI: 10.18043/ncm.82.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of Pedestrian Crashes on Vulnerable Populations in North Carolina

Abstract: T he health benefits of walking as a method of transportation include combatting the obesity epidemic by increasing physical activity [1] and reducing motorized transportation's contribution to air pollution [2]. In addition, walking provides an essential form of transportation for the estimated 9% of US households without access to a personal vehicle [3]. However, in the setting of non-pedestrian-centered transportation infrastructure, common in the United States, pedestrians are vulnerable road users who are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Recent studies combining police data with other sources have been done in North Carolina, Washington, D.C., and Oregon. Harmon et al developed an algorithm to link police crash reports with hospital emergency department records in North Carolina ( 16 ). Examining bicyclist injuries specifically, they found that 487 (43%) of 1,142 police-reported bicyclist crashes were linked to a hospital record.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies combining police data with other sources have been done in North Carolina, Washington, D.C., and Oregon. Harmon et al developed an algorithm to link police crash reports with hospital emergency department records in North Carolina ( 16 ). Examining bicyclist injuries specifically, they found that 487 (43%) of 1,142 police-reported bicyclist crashes were linked to a hospital record.…”
Section: Literature Reviewmentioning
confidence: 99%